Jill Posener : Spray It Loud. (London-Boston : Routledge & Kegan Paul, 1982)
Contents : 1. Women's Writes ; 2. Persons Unknown ; 3. The Front Line ; 4. Who Needs Housing? ; 5. The Paw Relations ; 6. Protest and Survive ; 7. You Smoke, I Choke ; Trouble with the Law
Engels
boek
Keywords: Posener, Jill